2013
DOI: 10.1530/eje-13-0101
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits goitrogenous effects of type 2 diabetes

Abstract: Objective: Data on the association between type 2 diabetes mellitus (T2DM) and thyroid volume are sparse. An experimental study demonstrated an inhibitory effect of metformin on the growth of human thyroid cells. So far no study on humans has investigated potentially modulating effects of metformin on the association between T2DM and thyroid volume. Therefore, we investigated these effects in a population-based cohort study. Design and methods: We used data from the Study of Health in Pomerania and included 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 25 publications
2
14
0
3
Order By: Relevance
“…A possible effect of metformin therapy in lowering serum thyroid‐stimulating hormone concentrations in people with diabetes and primary hypothyroidism has been suggested and this may be supported by recent evidence that metformin inhibits goitre formation in people with Type 2 diabetes . While the association between metformin usage and a lower prevalence of hypothyroidism does not necessarily imply a ‘protective’ effect of metformin therapy, the results of the present simple survey raise this possibility.…”
Section: Discussionsupporting
confidence: 66%
“…A possible effect of metformin therapy in lowering serum thyroid‐stimulating hormone concentrations in people with diabetes and primary hypothyroidism has been suggested and this may be supported by recent evidence that metformin inhibits goitre formation in people with Type 2 diabetes . While the association between metformin usage and a lower prevalence of hypothyroidism does not necessarily imply a ‘protective’ effect of metformin therapy, the results of the present simple survey raise this possibility.…”
Section: Discussionsupporting
confidence: 66%
“…Prospective and retrospective studies showed that patients with prediabetes and type 2 diabetes mellitus (T 2 DM) had a significantly increased thyroid volume and a higher prevalence of incident goiter and nodules. Furthermore, diabetic patients treated with metformin had a smaller thyroid volume and a lower risk for the formation of thyroid nodules when compared with controls (Anil et al 2013, Ittermann et al 2013, Blanc et al 2015. These results suggested that metformin exerts an anti-proliferative activity, providing a rationale for an innovative therapy of thyroid proliferative diseases with metformin.…”
Section: Introductionmentioning
confidence: 83%
“…Patients with IR have larger thyroid volumes and higher risk for formation of thyroid nodules, and higher circulating levels of insulin are thought to increase thyroid proliferation and formation of thyroid nodules (Ittermann et al 2013, Ogbera et al 2012. One study hereof worth mentioning showed that development of thyroid nodule may depend on IR: in patients with small benign thyroid nodules and IR, metformin therapy was accompanied by a reduction in the nodular size, which was paralleled by a fall in TSH (Rezzonico et al 2011).…”
Section: The Pathogenesis Of Thyroid Nodulementioning
confidence: 99%
“…In the population of patients with insulin resistance, metformin therapy resulted in a reduction in volume of thyroid and nodules [48]. In addition, Ittermann et al showed that type 2 diabetes patients treated with metformin have a lower thyroid volume compared to those treated with other hypoglycaemic agents [49]. Metformin also reduces the level of serum TSH, the main growth factor for thyroid cells [50].…”
Section: Goitre and Thyroid Cancermentioning
confidence: 99%
“…Ponadto, Ittermann i wsp. wykazali, że pacjenci z cukrzycą typu 2 leczeni metforminą mają mniejszą objętość tarczycy w porównaniu z leczonymi innymi lekami hipoglikemizującymi [49]. Metformina również poprzez działanie ośrodkowe zmniejsza stężenie TSH w surowicy krwi, głównego czynnika wzrostowego komórek tarczycy [50].…”
Section: Prace Poglądoweunclassified